1985
DOI: 10.1007/bf02541756
|View full text |Cite
|
Sign up to set email alerts
|

Kernel oils of seven plant species of zaire

Abstract: Kernels ofPentaclethra macrophylla, Allanblackia floribunda, Panda oleosa, Treculoa africana, Desplatzia dewevrei, Garcinia kola andMilletia laurentii were found to contain respectively 45.9, 67.6, 50.5, 11.8, 20.4, 2.1 and 22.9% oil (% dry matter). Gas liquid chromatography showed the major fatty acids of the kernel oils were as follows:P. macrophylla, 18:1 (31.3%) and 18:2 (40.4%);A. floribunda, 18:0 (55.9%) and 18:1 (43.3%);P. oleosa, 16:0 (32.0%), 18:1 (30.2%) and 18:2 (29.2%);T. africana, 16:0 (25.7%), 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Collected anthers were dried in an incubator at [20][21][22] • C until dehiscence, which usually took about 24 h and the germination tests were carried out immediately. Germination medium consisted of 1% agar and 15% sucrose, and prepared by dissolving them in boiling water at pH 5.6.…”
Section: Seed Parent and Pollen Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Collected anthers were dried in an incubator at [20][21][22] • C until dehiscence, which usually took about 24 h and the germination tests were carried out immediately. Germination medium consisted of 1% agar and 15% sucrose, and prepared by dissolving them in boiling water at pH 5.6.…”
Section: Seed Parent and Pollen Sourcesmentioning
confidence: 99%
“…Their oil percentage was determined according to the method of Foma and Abdola [20]. Fatty acid composition also was measured in accordance with the method of Kodad and Socias i Company [14].…”
Section: Fatty Acid Composition Oil Content and Fruit Characteristicsmentioning
confidence: 99%
“…Allanblackia trees produce large berry-like fruits that contain seeds (30 to 50) of high food, cosmetic and pharmaceutical importance (Foma andAbdala, 1985, Bonanome andGrundy, 1988). Allanblackia seeds are mainly obtained from collections of wild mature fruits that drop off the tree.…”
Section: Introductionmentioning
confidence: 99%
“…Allanblackia seeds are mainly obtained from collections of wild mature fruits that drop off the tree. The seeds contain about 72% white fat (Foma and Abdala, 1985) that remains solid at ambient temperatures and consists mostly of oleic and stearic acid (Eckey, 1954;Hilditch, 1958, cf http://www.fao.org/docrep/X5043E0d.htm). Oleic and stearic acids are reported to lower plasma cholesterol levels (Bonanome and Grundy, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Mature A. floribunda trees reach 30 m in height, 80 cm girth with bole straight and horizontal branches (Vivien and Faure 1996). Tallow tree is valued for its seeds, which are rich in hard fat (67-73%, Foma and Abdala 1985). This fat consists mostly of stearic and oleic acids (Hilditch et al 1940), which are reported to lower plasma cholesterol levels (Bonanome and Grundy 1988), thereby reducing the risks of heart attacks.…”
Section: Introductionmentioning
confidence: 99%